3D Modeling and Simulation Analysis of Cylindrical Indexing Cam based on CATIA - XiaTian; Chen Shaobo; Wang Jian; Ding Bingkun (Jixie chuandong)
Through the analysis of the cylindrical indexing cam working surface equations and parameters,combined the macro procedure of the CATIA secondary development,macro procedure of cam surface equations is written.The point coordinate of indexing period and rest period cam surface can be generated accurately and quickly by operating the macro.The cam curve and contour surface is generated through using the cloud shape and scanning function,thus the cam solid model can be generated.The motion simulation analysis of cam mechanism motion is carried out in CATIA.The evaluation of the established cam curve and contour surface is carried out,the precision cam curve and contour surface are obtained.